Receptor Tyrosine Kinases and Their Signaling Pathways as Therapeutic Targets of Curcumin in Cancer - Sudhesh Dev, Sareshma; Zainal Abidin, Syafiq Asnawi; Farghadani, Reyhaneh; Othman, Iekhsan; Naidu, Rakesh (Frontiers in Pharmacology, 2021)
Receptor tyrosine kinases (RTKs) are transmembrane cell-surface proteins that act as signal transducers. They regulate essential cellular processes like proliferation, apoptosis, differentiation and metabolism. RTK alteration occurs in a broad spectrum of cancers, emphasising its crucial role in cancer progression and as a suitable therapeutic target. The use of small molecule RTK inhibitors however, has been crippled by the emergence of resistance, highlighting the need for a pleiotropic anti-cancer agent that can replace or be used in combination with existing pharmacological agents to enhance treatment efficacy. Curcumin is an attractive therapeutic agent mainly due to its potent anti-cancer effects, extensive range of targets and minimal toxicity. Out of the numerous documented targets of curcumin, RTKs appear to be one of the main nodes of curcumin-mediated inhibition. Many studies have found that curcumin influences RTK activation and their downstream signalling pathways resulting in increased apoptosis, decreased proliferation and decreased migration in cancer both in vitro and in vivo. This review focused on how curcumin exhibits anti-cancer effects through inhibition of RTKs and downstream signalling pathways like the MAPK, PI3K/Akt, JAK/STAT and NF-κB pathways. Combination studies of curcumin and RTK inhibitors were also analysed with emphasis on their common molecular targets.